Direct seeding of rice in Punjab: Current status, performance and limitations - Singh, Gurpreet; Ranguwal, Sangeet; Kumar, Raj (Indian Farming, 2023)
As an alternative solution to the traditional puddled transplanted rice (PTR), the direct seeding of rice (DSR) is a viable alternative to overcome the problems of rising cultivation costs and declining water table for sustainable rice production. The DSR is yet to become an integral part of the farming system in Punjab. Easy availability of labour for transplanting paddy followed by lack of technical knowledge, diffidence in adopting DSR and non-availability of required machinery/ implements are the major reasons behind slow-adoption of DSR. For wider acceptance of DSR, there is a need to generate more awareness of recommended DSR production practices along with timely availability of required farm machinery on custom hiring basis, auxiliary research and development efforts.